Digital Financial Transformation and Efficiency in Islamic Banking Systems - Nofinawati SEI MA; Adanan Murroh Nasution (Journal of Islamic Financial Technology, 2025)
This article aims to systematically synthesize the relationship between digital financial transformation and efficiency in the Islamic banking system, by assessing how the adoption of digital technologies affects operational performance, sharia compliance, and the expansion of financial inclusion. This study uses an interpretive-constructivist paradigm-based systematic literature review approach to examine empirical and conceptual findings in various cross-border studies. The analysis was carried out on digitalization trends, sharia compliance governance models, as well as efficiency indicators such as Cost-to-Income Ratio, accuracy of customer assessment, transaction speed, profitability, and financial stability. The theoretical framework is enriched by the integration of the Three Lines of Defense and Digital Shariah Compliance Committee models. The literature synthesis shows that digital transformation consistently improves the efficiency of Islamic banks through reducing operational costs, increasing the accuracy of customer assessments, accelerating transactions, increasing customer satisfaction, and expanding access to finance, including for underserved groups. However, significant challenges remain, including digital infrastructure gaps, cybersecurity risks, limited human resources, the complexity of harmonizing technology with sharia principles, and the need for stronger digital governance. The study's main novelty lies in the development of an integrated conceptual framework that explains the multidimensional mechanisms of how digitalization affects operational efficiency and sharia compliance in Islamic banking. This approach fills in the gap of the previous literature that tends to be fragmented, and presents a comprehensive perspective on the role of technology in strengthening the competitiveness of the Islamic finance industry. These findings affirm the importance of strengthening digital governance, improving human resource digital competence, harmonizing regulations across jurisdictions, and modernizing sharia supervision to ensure that digital transformation takes place safely, inclusively, and sustainably. The study provides a theoretical and practical basis for regulators, academics, and industry to design effective digitalization strategies in Islamic banking.Keyword : Digital Financial Transformation, Efficiency, Islamic Banking Systems